Effects of prenatal alcohol exposure on the development of white matter volume and change in executive function - Gautam, P. (Elsevier, 2014)
Prenatal alcohol exposure can cause a wide range of deficits in executive function that persist throughout life, but little is known about how changes in brain structure relate to cognition in affected individuals. In the current study, we predicted that the rate of white matter volumetric development would be atypical in children with fetal alcohol spectrum disorders (FASD) when compared to typically developing children, and that the rate of change in cognitive function would relate to differential white matter development between groups. Data were available for 103 subjects [49 with FASD, 54 controls, age range 6–17, mean age = 11.83] with 153 total observations. Groups were age-matched. Participants underwent structural magnetic resonance imaging (MRI) and an executive function (EF) battery. Using white matter volumes measured bilaterally for frontal and parietal regions and the corpus callosum, change was predicted by modeling the effects of age, intracranial volume, sex, and interactions with exposure status and EF measures. While both groups showed regional increases in white matter volumes and improvement in cognitive performance over time, there were significant effects of exposure status on age-related relationships between white matter increases and EF measures. Specifically, individuals with FASD consistently showed a positive relationship between improved cognitive function and increased white matter volume over time, while no such relationships were seen in controls. These novel results relating improved cognitive function with increased white matter volume in FASD suggest that better cognitive outcomes could be possible for FASD subjects through interventions that enhance white matter plasticity.